2015
DOI: 10.3397/1/376317
|View full text |Cite
|
Sign up to set email alerts
|

Applications of AutoRegressive Integrated Moving Average (ARIMA) approach in time-series prediction of traffic noise pollution

Abstract: The paper analyzes the long-term noise monitoring data using the AutoRegressive Integrated Moving Average (ARIMA) modeling technique. Box-Jenkins ARIMA approach has been adapted to simulate the daily mean L Day (06-22 h) and L Night (22-06 h) in A-and C-weightings in conjunction with single-noise metrics, daynight average sound level (DNL) for a period of 6 months. The autocorrelation function (ACF) and partial autocorrelation function (PACF) have been obtained to find suitable orders of autoregressive (p) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…There has been no such previous study reported on the development of an ANN model for Delhi city, while for the other cities of [44][45][46][47][48][49]. Thus, it can provide a suitable substitute to cumbersome long-term noise monitoring and forecasting [50,51]. However, for such predictions, an exclusive and precise database of hourly vehicular density for each type of vehicles moving on roads, average speed of light and heavy vehicles etc., is a pre-requisite.…”
Section: Implications Of Developed Modelsmentioning
confidence: 96%
“…There has been no such previous study reported on the development of an ANN model for Delhi city, while for the other cities of [44][45][46][47][48][49]. Thus, it can provide a suitable substitute to cumbersome long-term noise monitoring and forecasting [50,51]. However, for such predictions, an exclusive and precise database of hourly vehicular density for each type of vehicles moving on roads, average speed of light and heavy vehicles etc., is a pre-requisite.…”
Section: Implications Of Developed Modelsmentioning
confidence: 96%
“…IoT must overcome some challenges to extract new insights from data [49]. In previous studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], environmental noise prediction mainly focused on the spatial propagation of noise, and there were few studies focused on the variation of noise in short-term. The noise data set used in this study is in seconds, which is more random.…”
Section: Proposed Lstm Model Frameworkmentioning
confidence: 99%
“…In recent years, with the widespread utilization of sound level meters and the development of various sensor network technologies, environmental noise data has an exploding expansion. Although there have been previous studies on noise measurement, prediction, and control [19,22,23,25,[33][34][35][36], most of the research data are relatively diminutive. This gave the inspiration to have a second thought about the environmental noise prediction problem, that is, whether there are more optimized noise prediction models and methods when handling an abundant amount of noise data.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, considering that the residual sequence contains certain noise and periodic components, a modified modeling method by extracting periodic component from the residual sequence of conventional statistical model is proposed in the study. Inspired by the application of singular spectrum analysis (SSA) in data processing [27][28][29][30] and the application of autoregressive integrated moving average (ARIMA) model in time series analysis, [31][32][33][34] the residual sequence obtained by conventional statistical model is processed and forecasted by SSA and ARIMA. Firstly, the conventional statistical model is established with stepwise regression model, and the residual sequence is reconstructed using the trend and periodic components extracted by SSA.…”
Section: Introductionmentioning
confidence: 99%